Improving the Retention of Maxillary Complete Denture: A Case Report - Hoaida Shawi,; Masarah Dirbal,; Shayyima Altireeki,; Amr Alriyani,; Zainal Arifin, (AlQalam Journal of Medical and Applied Sciences, 2024)
Complete dentures play an essential role in restoring oral function and improving the quality of life for individuals who have missing all their normal teeth. One of the key factors determining the success of complete dentures is their retention, which refers to the ability of dentures to stay securely in place during normal oral function. Adequate retention is essential for proper speech, mastication and overall comfort of the denture wearer. The study aimed to improve the retention of complete dentures through three different approaches: spacer, posterior palatal seal area, and undercut area. Three dentures were fabricated using the same steps, with variations in certain steps based on the retention technique being employed. The study showed that all three dentures had improved retention compared to standard complete dentures. The dentures that included the posterior palatal seal area and spacer demonstrated higher retention than the denture that employed the undercut technique. It is worth noting that the patient did not find the denture with the undercut technique satisfactorily. تلعب أطقم الأسنان الكاملة دورًا أساسيًا في استعادة وظيفة الفم وتحسين نوعية الحياة للأفراد الذين فقدوا جميع أسنانهم الطبيعية. أحد العوامل الرئيسية التي تحدد نجاح أطقم الأسنان الكاملة هو الاحتفاظ بها، وهو ما يشير إلى قدرة أطقم الأسنان على البقاء بشكل آمن في مكانها أثناء وظيفة الفم الطبيعية. يعد الاحتفاظ الكافي ضروريًا للكلام السليم والمضغ والراحة العامة لمرتدي طقم الأسنان. هدفت الدراسة إلى تحسين الاحتفاظ بأطقم الأسنان الكاملة من خلال ثلاث طرق مختلفة: المباعد، منطقة الختم الحنكي الخلفي، والمنطقة السفلية. تم تصنيع ثلاثة أطقم أسنان باستخدام نفس الخطوات، مع وجود اختلافات في خطوات معينة بناءً على تقنية الاحتفاظ المستخدمة. أظهرت الدراسة أن أطقم الأسنان الثلاثة جميعها قد حسنت الاحتفاظ مقارنة بأطقم الأسنان الكاملة القياسية. أظهرت أطقم الأسنان التي شملت منطقة الختم الحنكي الخلفي والمباعد احتفاظًا أعلى من طقم الأسنان الذي استخدم تقنية التقويض. ومن الجدير بالذكر أن المريض لم يجد طقم الأسنان بتقنية التقطيع بشكل مرضي